Expression of Pannexin1 in the outer plexiform layer of the mouse retina and physiological impact of its knockout - Kranz, Katharina; Dorgau, Birthe; Pottek, Mark; Herrling, Regina; Schultz, Konrad; Bolte, Petra; Monyer, Hannah; Penuela, Silvia; Laird, Dale W.; Dedek, Karin; Weiler, Reto; Janssen‐Bienhold, Ulrike (The journal of comparative neurology, 2013)
Pannexin1 (Panx1) belongs to a class of vertebrate proteins that exhibits sequence homology to innexins, the invertebrate gap junction proteins, and which also shares topological similarities with vertebrate gap junction proteins, the connexins. Unlike gap junctional channels, Panx1 forms single-membrane channels, whose functional role in neuronal circuits is still unsettled. We therefore investigated the subcellular distribution of Panx1 in the mouse retina of wildtype and Panx1-null mice by reverse-transcription polymerase chain reaction (RT-PCR), immunohistochemistry, and electron microscopy. Use of Panx1-deficient mice served as a model to assess the physiological role of Panx1 by electroretinographic recordings and also to ensure the specificity of the anti-Panx1 antibody labeling. Expression of Panx1 was found in type 3a OFF bipolar cells and in dendrites and axonal processes of horizontal cells. Panx1 was also found in horizontal cell dendrites representing the lateral elements of the triad synapse at cone and rod terminals. In vivo electroretinography of Panx1 knockout mice indicated an increased a- and b-wave compared to Panx1 wildtype mice under scotopic conditions. The effect on the b-wave was confirmed by in vitro electroretinograms from the inner retina. These results suggest that Panx1 channels serve as sinks for extracellular current flow making them possible candidates for the mediation of feedback from horizontal cells to photoreceptors. J. Comp. Neurol. 521:1119-1135, 2013. © 2012 Wiley Periodicals, Inc.
Published online September 10, 2012
Gesehen am 03.11.2021